Aluminum alloy castings properties, processes, and applications - Kaufman, J. G. 1931- (ASM International, 2004)
Aluminum Alloy Castings provides property and performance data for all types of aluminum alloy castings and reviews and describes the factors that contribute to and affect those properties, including composition, microstructure, casting process, heat treatment, and quality assurance. The volume features extensive collections of property and performance data, including previously unpublished aging response curves, growth curves, and fatigue curves. These data are presented in consistent formats to enable easy comparisons among different alloys and tempers. The authors have endeavored to address all of the casting process technologies available for aluminum alloys. Engineering information is included for expendable mold, permanent mold, and pressure die casting processes and their variations. The focus of the process coverage is to review the effects of process selection and process variables on casting properties and performance. Representative examples of aluminum castings applications are provided. This book will be of significant value to materials and design engineers involved in the evaluation, selection and specification of aluminum casting applications and to casting producers as a means of better understanding, quantifying, improving, and promoting the performance characteristics of aluminum castings.
"American Foundry Society."
Keywords: Aluminum alloys -- Mechanical properties.; Aluminum castings.; elektronické knihy; electronic books